1995
DOI: 10.1007/bf00860748
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy in children: indications, technique and efficacy in 119 consecutive cases

Abstract: Consecutive renal biopsies were performed on native kidneys in 109 children and adolescents, aged 0.1-19.8 (mean 9.9) years (119 biopsies). Bleeding diatheses were excluded or treated pre-operatively with intravenous desmopressin acetate. Biopsies were performed by a radiologist under ultrasound imaging, using an automated spring-loaded device allowing selection of the length of the needle movement and score size. Diagnostically adequate tissue was retrieved in 118 of 119 (99.2%) biopsy procedures; 24-h post-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
36
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 12 publications
7
36
0
Order By: Relevance
“…To our knowledge, the current study is the only nationwide registry-based and largest report of renal biopsy complications, and our findings confirm the general impression of low complication rates and improved safety of modern renal biopsy procedures (19). Similar low complication rates have been reported in recent studies (16,19,20) in contrast to earlier studies (reporting 5%-7% complication rates) (21)(22)(23)(24)(25). The crucial safety evaluation of kidney biopsies is characterized by the overall risk and frequency of major complications, which in our study, are defined as need of blood transfusion and/or surgery or catheterbased intervention (embolization) secondary to bleeding, and they should not be jeopardized by procedural events of minor clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, the current study is the only nationwide registry-based and largest report of renal biopsy complications, and our findings confirm the general impression of low complication rates and improved safety of modern renal biopsy procedures (19). Similar low complication rates have been reported in recent studies (16,19,20) in contrast to earlier studies (reporting 5%-7% complication rates) (21)(22)(23)(24)(25). The crucial safety evaluation of kidney biopsies is characterized by the overall risk and frequency of major complications, which in our study, are defined as need of blood transfusion and/or surgery or catheterbased intervention (embolization) secondary to bleeding, and they should not be jeopardized by procedural events of minor clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
“…Male predominance in biopsy-proven kidney diseases corresponds with the data published by other authors (1, 6, 8, 10, 25, 30, 31). The patients' mean age of 12.77 ± 4.17 years at the time of RB is very similar to most other observations, where the mean age ranged from 9 to13 years (1,7,12,15,20,23,30,35). The significantly lower age of patients with MCD and IgM nephropathy was related to the onset of NS, in particular steroid-dependent nephrotic syndrome.…”
Section: Discussionsupporting
confidence: 88%
“…We recorded similar (3,15,22) and even lower rates of post-biopsy complications compared with the experience of other authors (2,6,7,28,32).…”
supporting
confidence: 86%
“…A similar observation has been reported by other authors using needles of identical gauges [5]. The adequacy of the biopsy material also compared favorably with other reports in the literature [6,7,12] regardless of the technique used [5,13].…”
Section: Discussionsupporting
confidence: 78%
“…A small perirenal hematoma was observed in 2 (5%) of our patients. Other authors [9] also reported a low incidence of this minor complication, though other minor complications like local pain or discomfort are not uncommon [6]. In patients with coagulation defects the risk of postbiopsy bleeding can be reduced by fresh frozen plasma infusion and vitamin K. Various sizes and types of needles have been used by different authors [4,10,11] with the aim to minimize bleeding complications.…”
Section: Discussionmentioning
confidence: 99%